Value of right ventricular dimensions' swings on weaning from mechanical ventilation - Soheir Mostafa Kasem Ahamed; Muhammad Hossam El-Din Hassan Maghrapy; Khaled Mohamed Ali Shehata; Samiaa Hamdy Sadek; Samir El-Hadidy Tawfek (SpringerOpen, 2019)
Background Cardiac dysfunction is a common cause of weaning failure. Previous studies focused on the role of LV diastolic dysfunction in the occurrence of weaning failure, and there are no more studies yet interested in RV dysfunction. Herein we evaluate cardiac changes using tissue Doppler echocardiography in critically ill patients during the weaning process and to compare between left and right ventricular functions as a predictor of weaning failure from mechanical ventilation. Methods We recruited 40 mechanically ventilated patients admitted to our ICU in this cross-sectional study. Echocardiography was performed during baseline ventilator settings and during spontaneous breathing trial (SBT) to assess changes in cardiac dimensions and functions. of left and right ventricular contractility and relaxation in this subset of patients. Results Among 40 patients included, there was a significant increase in cardiac dimensions during SBT. There was a statistically significant decrease in LV EF with (P=0.000) during SBT. Also, there was a statistically significant decrease in RV systolic function during SBT. There was a significant increase in the E/E' ratio of lateral mitral annulus due to the evolution of impaired LV relaxation and diastolic dysfunction (P=0.008). Moreover, the development of right ventricular diastolic dysfunction presented by E/E' ratio of tricuspid annulus, (P value=0.03). Conclusions RV dysfunction, as detected by systolic wave velocity of anterior tricuspid annulus (S') by Doppler tissue imaging during SBT, also has good sensitivity and specificity in weaning failure prediction from mechanical ventilation.